Engineering Systems and Networks The Way Ahead for Industrial Engineering and Operations Management - Amorim, Marlene; Ferreira, Carlos; Vieira Junior, Milton; Prado, Carlos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers a selection of the best papers presented at the joint international conference ICIEOM-CIO-IIE 2015, offering recent research on industrial engineering, management and operations from an international and interdisciplinary perspective. It includes contributions from different fields, such as operations research, modeling and simulation, production and service management and logistics, information systems and quality, and as such is of interest to both researchers and practitioners. Reflecting the interconnected nature of today's production systems, characterized by intense flows of goods, information and individuals between companies and nations, it is a valuable resource for anyone wanting an in-depth understanding of the field to guide managerial practice in order to take full advantage of existing opportunities.
Part 1 OR, Modelling and Simulation -- Analysis and Simulation of a Cork Transformation System -- Discovering Bayesian Networks using Process Mining: an Application in Manufacturing -- Forecasting Cloud Computing: Producing a Technological Profile -- Part 2 Logistics, Production and Information Systems -- A decision support framework for Production Flow Coordination using Supply Chain -- A Greedy Primal-Dual Type Heuristic to Select an Inventory -- A model that integrates direct and reverse flows in omnichannel logistics networks Control Policy -- Part 3 Quality and Management in Engineering Systems and Networks -- Characterising knowledge workers' job positions -- Information quality in companies committed to TQM -- Performance Measurement Systems for designing and managing Interoperability Performance Measures: A literature analysis -- Part 4 Education in Engineering Systems and Networks -- Agents playing the Beer Game: Solving the Production Dilemma through the Drum-Buffer-Rope Methodology.-Organizational Engineering: the emerging stage of Industrial Engineering etc.
Keywords: Industrial engineering; Production engineering; Operations research; Management science; Project management; Industrial and Production Engineering; Operations Research, Management Science; Project Management